Diversity and geographic distribution of spittlebugs (Homoptera: Cercopidae) associated with graminoids in Colombia and Ecuador - PECK, DANIEL C. (Revista Colombiana de Entomología, 2001)
The diversity and geographic distribution of spittlebugs (Homoptera: Cercopidae) associated with wild and cultivated graminoids were analyzed in order to summarize and divulge new information on the distribution, host plants, and nomenclature of the economically important species. Distribution records of spittlebug species were obtained from field collections and observations as well as the revision of specimens in four different museum collections. Data were obtained for 21 of the 32 Colombian departments and nine of the 20 Ecuadorian provinces. The presence of 15 species in Colombia and eight in Ecuador was confirmed for a total of 18 species from seven genera: Aeneolamia, Jsozulia, Mahanarva, Notozulia, Prosapia, Sphenorhina, and Zulia. A change in nomenclature was found for Z. carbonaría, incorrectly known in Colombia as Z. colombiana. Seven species were reported for the first time in Colombia. Two of those are new species, Mahanarva sp. nov. from the Amazonia of Colombia and Ecuador and coastal Ecuador, and Zulie sp. nov. from the Pacific Coast of Colombia and Ecuador. Another species, N. entreriana in the Dept. of Meta, represents a possible introduction from Brazil, and the species P simulans in the Dept of Valle del Cauca represents a possible new invader from Central America. The host list for Colombia and Ecuador includes 26 species of graminoids. For each spittlebug species the host plants, distribution at the level of the country, department, and province, and taxonomic notes are summarized. Given that the composition of the spittlebug complex varíes substantially among regions, the implications of this taxonomic diversity for pest management are discussed.